Pengembangan Media Video Pembelajaran Elaborate Table Set Up Untuk Siswa Perhotelan SMKS Pariwisata Triatma Jaya Singaraja - Semardiani, Ni Komang Ari; Sukerti, Ni Wayan; Kusyanda, Made Riki Ponga (Universitas Mathla'ul Anwar Banten, 2025)
This study aimed to: (1) describe the stages of developing a video -based learning medium for the F&B Service practice of Elaborate Table Set-Up at Sekolah Menengah Kejuruan Swasta Pariwisata Triatma Jaya Singaraja using the 4D development model (Define, Design, Develop, Disseminate). This research employed a Research and Development (R&D) design with the 4D model. The respondents consisted of 31 Year XI Hospitality students who had completed the Food and Beverage Service subject. Data were collected through a Likert-scale questionnaire administered to experts and students. The data were analysed using descriptive quantitative methods. The development process followed four systematic stages: (a) define, by identifying learning needs through observation, preliminary–final analysis, student analysis, task analysis, and concept analysis; (b) design, by preparing the material, determining the medium, selecting the format, and creating the initial design; (c) develop, by adding audio elements and conducting validation by material, media, and design experts; and (d) disseminate, by distributing the instructional video on a limited scale to teachers and students, and collecting students’ responses. The learning video is rated as highly feasible by experts, with a score of 100% from material experts and 96.81% from media and design experts. Students’ responses to the video are very positive, with a score of 95.6%. The results indicate that the developed video-based learning medium meets the criteria for both quality and effectiveness in supporting F&B Service learning.